Unmasking the Network: The Power Dynamics Behind the Social Movement Against Election Postponement - Dewi, Evie Ariadne Shinta; Diyaulmuhana, Diyaulmuhana; Pratamawaty, Benazir Bona (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
This study analyzes and visualizes the network dynamics of the